Towards Optimal Health Through Boredom Aversion Based on Experiencing Psychological Flow in a Self-Directed Exercise Regime—A Scoping Review of Recent Research - Carol Nash (Sports, 2025)
Background: Optimal health requires self-direction for exercise regime consistency. Boredom may cause abandoning regular exercise. Experiencing psychological flow—a concept psychologist Csikszentmihalyi originated—may avert boredom. Method: A search of post-2020 peer-reviewed publications following the PRISMA-ScR guidelines for scoping reviews investigates the range of research on this topic. The databases searched are OVID, ProQuest, PubMed, Scopus, Web of Science, and Google Scholar. The keywords are “Csikszentmihalyi AND flow AND exercise AND boredom”. Included returns contain all the keywords. Those excluded are reviews, books, reports missing any keywords, non-English reports, reports not based on research studies, and research published before 2020. Results: Two databases returned the included results: OVID (n = 3) and Google Scholar (n = 8). Conclusions: (1) Boredom is not evident when experiencing exercise-programme psychological flow. (2) Psychological flow evolves with self-directed changes in an exercise programme. (3) Successful exercise programme modifications during COVID-19 considered the imposed limitations. (4) Exercise regimes that are neither excessive nor extreme promote optimal health. And (5) optimal health accounts for exercise skill level and gender. Additionally, cognitive bias is avertable with a research team. Studies should include the research date and location and how flow reduces boredom, permitting accurate comparisons.